Maintenance engineering and management (CIBSE guide, 2020)
Building services engineers provide the internal environmental conditions that enable business processes to function at an optimum level while providing a safe, comfortable environment for occupants to achieve their maximum performance potential. Effective maintenance and operation is a key factor in ensuring this continues for the life of the building. This guidance is a continuation of work by the CIBSE Maintenance Task Group, Chaired by Joanna Harris, and is intended for the benefit of all those involved in the operation and maintenance of engineering services. It is an update of the 2008 Guide and aims to provide best practice for those who have responsibility for the management and maintenance of the engineering services in a building. It also aims to inform those who design and construct buildings and raise awareness of the implications their decisions have on enabling effective management and maintenance Principal areas of revision relate to legislation changes and changes in best practice.